Consumption modeling based on Markov chains and Bayesian networks for a demand side management design of isolated microgrids. (20th August 2016) - Roje, Tomislav; Marín, Luis G.; Sáez, Doris; Orchard, Marcos; Jiménez‐Estévez, Guillermo
Summary: This paper proposes a novel simulator of energy consumption patterns that allows designing demand side management (DSM) strategies without economic incentives. The simulator emulates consumers' patterns with and without installed DSM interfaces, based on both actual consumption measurements and surveys applied to the inhabitants of an existing isolated microgrid (Huatacondo, Chile) that has a particular DSM strategy without economic incentives. The simulator uses Markov chains to generate data characterizing consumption patterns without DSM and Bayesian networks for cases in which the users respond to the DSM strategy. Data obtained from the simulator are used to derive a response model of the consumers to the DSM interface, which can be included for the energy management system design. Results show that the implemented strategy can be effective and can generate savings up to 4.45% in diesel consumption for an ideal case where all the dwellings have the interface installed. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A novel simulator of energy consumption patterns that allows designing demand side management (DSM) strategies without economic incentives is proposed. Consumption patterns without DSM are characterized by Markov chains and the users' response to the DSM strategy by Bayesian networks. A response model of the consumers from the simulator is derived, which can be included for the energy management system design. Results show that the proposed strategy can be effective and can generate economical savings for the microgrid operation.